Predicting Physical Activity Behaviours Among Obese High School Students In Ji Lin Province, China - Zhou, Jianming (2023)
This study investigates the factors that predict physical activity behaviour among high school students in Chang Chun City, Ji Lin Province, China. A stratified random sampling technique was used to collect data from 6,000 respondents in three areas, fifteen schools in Chang Chun City, Ji Lin Province, China (CCJLC). The stratification was applied based on three kinds of types of areas, respectively urban, suburban, and rural.